Prophylactic Use of Ketamine and Tramodol for the Prevention of Intra-Operative Shivering in Lower Limb Surgeries Done in Spinal Anesthesia (Medical Forum Monthly, 2020)
Objective: To determine the efficacy of prophylactic intravenous ketamine in the prevention of shivering during spinal anesthesia for elective lower limb surgery.Study Design: Comparative study.Place and Duration of Study: This study was conducted at the Department of Anesthesia, Allied hospital, Faisalabad and Anesthesia Department, PIC, Lahore from 30th Oct. 2019 to 30th April 2020.Materials and Methods: Vital monitoring was done using standard monitoring equipment on hourly basis and later more frequently during the spinal procedure till the next half an hour. Body temperature was noted before, during and after the procedure at regular interval to rule out any hypo- or hyperthermia. The room temperature was controlled and was kept between 24-260C along with humidification of the theatre. Patients were divided into three groups: first group receiving intravenous (IV) bolus normal saline (Group S, n = 30) or second group of intravenous ketamine 0.5mg/kg (Group K, n=30) and third group of tramodol 0.5mg/kg (Group T, no=30).Results: No of patients who had intra operative shivering was found to be significantly less in Group K as compared to that in Group S. On further analysis of patients in the Group S, 18 patients had grade 2 shivering level and had to be injected with tramadol after shivering was observed. In Group K, 3 patients reached grade 2 shivering. In Group T, 2 patients reached grade 2 (p<0.001). At 30min after spinal anesthesia, there were no differences between the groups regarding grade of shivering. None of the patients required a second dose of tramodol for grade 2 shivering within 30 min period after spinal anesthesia. Three patients in Group S, one patient in Group K and one patient in Group T had nausea (p>0.05).Conclusion: Prophylactic intravenous ketamine has a similar clinical efficacy compared to that of intravenous tramodol in preventing shivering during spinal anesthesia in elective lower limb surgery. There were no significant changes in the hemodynamic parameters and adverse effects.